Fostering Learner Mobility Between Engineering Education and a Twenty First Century Workplace - Abu-aisheh, Akram Ahmad; Grant, Lynroy (International Journal of Advanced Corporate Learning (iJAC), 2011)
Engineering education today is undergoing unprecedented array of challenges, especially in the teaching and learning process. Among other challenges in this area students now require multiple stimuli, they have very low tolerance for monotonous static content, and they are highly mobile. To address some of these challenges, the authors have conducted a pilot study with Learner Agent Objects (LAO) individual portfolios. LAO portfolios are collections of artifacts (studentsâ?? best work) representing a learner’s academic experience. LAO affords a foundation for creating a more comprehensive and seamless movement of learners between jurisdictions in engineering education and the workplace. A more seamless movement of individuals between formal education, informal education and the workplace has significant implications for the learning environments and ecosystems of engineers as lifelong learners.